Electrospun polytetrafluoroethylene (PTFE) fibers in membrane distillation applications - Charles Defor; Shih-Feng Chou (AIMS Materials Science)
Polytetrafluoroethylene (PTFE) is a fully fluorinated linear polymer with a (CF2-CF2)n backbone. High molecular weight PTFEs are chemically inert while possessing excellent hydrophobic surface properties attributed to their low surface energy. These characteristics make PTFE an excellent candidate for membrane distillation application among all other hydrophobic polymers. In this review, the electrospinning processes of PTFE fibers are discussed in detail with a focus on various electrospinning effects on the resulting fiber morphologies and structures. Due to the high chemical resistance and low solvent solubility, PTFE is typically electrospin with a polymer carrier, such as polyvinyl alcohol (PVA) and/or polyethylene oxide (PEO), using emulsion electrospinning followed by a sintering process. The amount of PTFE in emulsion, types of polymer carriers, electrospinning parameters, and sintering conditions have interconnected effects on the resulting morphological structures of PFTE fibers (e.g., beading or continuous fibers). In addition, electrospun PTFE fibers are further functionalized using methods of co-electrospinning with other hydrophobic polymers as well as incorporations of metallic (ZnO) and inorganic particles (POSS) to improve their performance in membrane distillation. Water contact angles, permeation fluxes, salt rejection rates, and hours of operations are reported for various functionalized electrospun PTFE fibrous membranes to demonstrate their feasibility in membrane distillation applications. In general, this article provides a scientific understanding of electrospun PTFE fibers and their engineering application in membrane distillation.